Bayesian Inference of Phylogeny and Its Impact on Evolutionary Biology - Huelsenbeck, John P.; Ronquist, Fredrik; Nielsen, Rasmus; Bollback, Jonathan P. (Science (American Association for the Advancement of Science), 2001)
As a discipline, phylogenetics is becoming transformed by a flood of molecular data. These data allow broad questions to be asked about the history of life, but also present difficult statistical and computational problems. Bayesian inference of phylogeny brings a new perspective to a number of outstanding issues in evolutionary biology, including the analysis of large phylogenetic trees and complex evolutionary models and the detection of the footprint of natural selection in DNA sequences.